FAZLUR RAHMAN DAN METODE IJTIHADNYA: Telaah Sekitar Pembaruan Hukum Islam - Alyafie, Husein (Institut Agama Islam Negeri (IAIN) Palu, 2009)
In his monumental work, Islamic Methodology in History, Fazlur Rahman proposed two causes of failure of using ijtihÃ¢d as a method in interpreting Islamic law among classical Islamic law scholars. Firstly, there is an unharmonious relationship between âsunnah-ijmaâ-ijtihÃ¢d; secondly, there is a burden of majority doctrine theologyÂ towards the law. Both causalities are related each other. Fazlur Rahman tried to show the unharmonious between âsunnah-ijmaâ-ijtihÃ¢dâ as stated in usÃ»l fiqh. In those unharmonious relationship, ijtihÃ¢d is defeated by ijmaâ. In fact, ijtihÃ¢d is regarded as a means to direct and to form ijmaâ. Due to the ineffective position of ijtihÃ¢d, it is not possible to form new ijmaâ.Kata Kunci: Fazlur Rahman, metode ijtihad, pembaruan hukum Islam, sunah, ijmak